2008
DOI: 10.1086/587810
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Surgical Site Infection After Low Transverse Cesarean Section

Abstract: background. Independent risk factors for surgical site infection (SSI) after cesarean section have not been well documented, despite the large number of cesarean sections performed and the relatively common occurrence of SSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
190
4
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(226 citation statements)
references
References 24 publications
(33 reference statements)
18
190
4
14
Order By: Relevance
“…S urgical site infection after spine surgery is an uncommon but well-known complication that can result in a poor outcome, arthrodesis-site nonunion, and neurological injury [1][2][3][4][5][6][7] . In the setting of a surgical site infection, patients are likely to require intravenous (IV) antibiotics, a prolonged hospital stay 8 , and operative debridement.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…S urgical site infection after spine surgery is an uncommon but well-known complication that can result in a poor outcome, arthrodesis-site nonunion, and neurological injury [1][2][3][4][5][6][7] . In the setting of a surgical site infection, patients are likely to require intravenous (IV) antibiotics, a prolonged hospital stay 8 , and operative debridement.…”
mentioning
confidence: 99%
“…The deleterious clinical effects of surgical site infection are associated with an increase in total costs 1 . Previous studies have shown that age, diabetes, obesity, and surgical approach and invasiveness are risk factors for surgical site infection [3][4][5][6][7] . The association of surgical invasiveness and increased risk for surgical site infection is fairly intuitive but has been poorly defined in the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Duration of membrane rupture [16,17], increasing maternal body mass index [18][19][20], incision length and corticosteroid use [21] have been previously reported as a risk factor for postcesarean infection. Studies have reported inconsistent results on risk for maternal infection after classical compared to low-transverse uterine incisions.…”
Section: Discussionmentioning
confidence: 99%
“…Per cutaneous coronary catheterization (PCI) within 90 min in ST elevation myocardial infarction (STEMI) [4] Preventive aspirin therapy for patients with acute MI [5] Preventive statins therapy for patients with acute MI [6] Performance evaluation of risk of stroke in patients with atrial fibrillation [7] Evaluation of Padua score for prevention of venous thrombosis [8] Carotid arteries duplex within 72 h of admission to the emergency department due to transit ischemic attack [9] TPA or neuro-angiography after acute CVA [10] Preventive antibiotic treatment an hour before colectomy [11] Operation of hip fracture within 48 h of admission [12] Antibiotic prophylaxis before hip surgery [13] Preventive antibiotic treatment before Cesarean section [14] Preventive anti-thrombotic treatment before hysterectomy [15] Steroids therapy for women at risk of preterm delivery [16] Hospitalization within two weeks after gynecologic elective surgery [17] Hospitalization within two weeks after elective cesarean section [18] Readmissions to the emergency department within 24 h [19] Computing diagnosis in the emergency department, brain CT or MRI in acute CVA within 25 min of arrival to the emergency department [20] Chest x-rays interpretation NA Central line associated bloodstream sepsis (CLABSI) for 1,000 catheter-days [21] Clostridium difficile incidence for 1,000 hospitalization days [22] Falls for 1000 hospitalization days [23] Falls with severe damage for 1000 hospitalization days [24] Acquired pressure sore [24] Computing main diagnosis in the digital patient's file NA Longer hospitalization of more than 8 days following colectomy for colorectal cancer [25] Readmission within 2 weeks after trans urethral prostatectomy [26] Planned patient's discharge NA…”
Section: Indicator Referencesmentioning
confidence: 99%